2014
DOI: 10.1063/1.4903500
|View full text |Cite
|
Sign up to set email alerts
|

Effects of potassium doping on solution processed kesterite Cu2ZnSnS4 thin film solar cells

Abstract: Alkaline metals doping is one of the approaches for achieving high efficiency Cu(In,Ga)Se2 (CIGS) solar cell. Recently, potassium doping helps to break the record efficiency of CIGS solar cell doped with sodium. In this paper, we have investigated how incorporation of potassium can influence the properties of Cu2ZnSnS4 (CZTS) thin film and the performance of resulting solar cell. Our results showed that K doping can enhance the (112) preferred orientation, increase the grain size and reduce the second phase Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
70
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 29 publications
6
70
2
1
Order By: Relevance
“…[ 2a , 8 ] The (112) preferred orientation and crystallinity of the CZTS fi lms are enhanced through doping K atoms, and in addition, some secondary phases such as ZnS are also surpressed. [ 8 ] Because of the high concentration of Ca within soda lime glass, its effect on the CZTS devices have also been investigated. [ 9 ] However, no obvious infl uences on CZTS device performance were observed, which was attributed to the +2 oxidation state of Ca.…”
Section: Doi: 101002/aenm201502386mentioning
confidence: 99%
“…[ 2a , 8 ] The (112) preferred orientation and crystallinity of the CZTS fi lms are enhanced through doping K atoms, and in addition, some secondary phases such as ZnS are also surpressed. [ 8 ] Because of the high concentration of Ca within soda lime glass, its effect on the CZTS devices have also been investigated. [ 9 ] However, no obvious infl uences on CZTS device performance were observed, which was attributed to the +2 oxidation state of Ca.…”
Section: Doi: 101002/aenm201502386mentioning
confidence: 99%
“…9,18) Moreover, some reports claimed that Na doping enhances the crystallinity of absorber thin films and the short-circuit current of thin-film solar cells. [19][20][21] Although the positive effects of Na doping in CIGS-based solar cells have been extensively studied, those in CZTSbased solar cells are still unclear.…”
mentioning
confidence: 99%
“…[7] First studies on the effect of potassium addition confirmed advantageous effects on kesterite absorber growth and optoelectronic properties similar to Na. [8,9] Several studies comparing different alkali elements and their effect on solar cell properties and device performance have recently been published. [10][11][12][13] Table 1 compares the effects on device performance by extracting a ranking of the various alkali elements in each publication in the order of their capability to improve device performance.…”
mentioning
confidence: 99%